2021
DOI: 10.3390/v13030521
|View full text |Cite
|
Sign up to set email alerts
|

Blood Counts, Biochemical Parameters, Inflammatory, and Immune Responses in Pigs Infected Experimentally with the African Swine Fever Virus Isolate Pol18_28298_O111

Abstract: This study aimed to indicate the influence of infection caused by genotype II African swine fever virus (ASFV)–isolate Pol18_28298_O111, currently circulating in Poland, on blood counts, biochemical parameters, as well as inflammatory and immune responses. Blood and sera collected from 21 domestic pigs infected intranasally with different doses of virulent ASFV were analysed. The infection led to variable changes in blood counts depending on the stage of the disease with a tendency towards leukopenia and throm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 46 publications
10
14
0
Order By: Relevance
“…Our study does not exclude the role of anti-ASF antibodies in the productive immune response to ASFV in vivo , since all examined sera were collected from survivor animals. This and a previously published study ( 31 ) underline the importance of possible interactions between humoral and cellular immunity in protection against the disease.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Our study does not exclude the role of anti-ASF antibodies in the productive immune response to ASFV in vivo , since all examined sera were collected from survivor animals. This and a previously published study ( 31 ) underline the importance of possible interactions between humoral and cellular immunity in protection against the disease.…”
Section: Discussionsupporting
confidence: 81%
“…All serum donors were considered potential ASF survivors. Different clinical symptoms but a constant and low virus load in the blood had been recorded in the selected pigs during animal experiments conducted previously ( 31 , 32 ). The evolution of the viraemia of survivor pigs is shown in Fig.…”
Section: Methodsmentioning
confidence: 85%
See 2 more Smart Citations
“…Previous studies showed that virulent ASFV infection could promote the release of acute-phase proteins in serum, including serum amyloid A (SAA) and C-reactive protein (CRP), and increase the expression of a number of inflammatory cytokines, such as IL-1α, IL-1β, IL-6, and TNF-α ( Sanchez-Cordon et al, 2007 ; Walczak et al, 2021 ). Similarly, Wang et al (2020) found that virulent SY18 ASFV infection induced a robust and sustained elevation of pro-inflammatory cytokines (such as TNF-α, IL-1β, IL-6, IL-18, RANTES, and IP-10) from 3 days post-infection (dpi) and a secondary drastic increase including TNF-α, IL-1β, IL-6, and IL-8 and IL-10 at the terminal phase of infection in domestic pigs.…”
Section: African Swine Fever Virus Immune Evasion Mechanisms and Their Relationship To Live Attenuated Vaccinesmentioning
confidence: 99%